Relationship between maternal and newborn endothelial function and oxidative stress (2015)
Objective To evaluate the Relationship between maternal and newborn endothelial function and oxidative stress. Methods Forty-three pregnant women and their offspring were evaluated. As markers of endothelial function, the flow-mediated dilation (FMD) was measured in pregnant women in the second and third trimesters, and nitric oxide (NO) was quantified in the endothelial cells of the umbilical cord vein. Malondialdehyde (MDA), as a marker of oxidative stress, was measured in the maternal plasma (second and third trimesters) and plasma from umbilical cord blood. Gestational age and birth weight were recorded. Correlations between variables were estimated, and adjustments were made for specific gestational week of measurement, gestational age at birth, and complications during pregnancy and/or at delivery.